Effects of Corporate Social Responsibility on The Performance of Vietnamese Seafood Exporting Enterprises. - NGUYEN, THI THU THUY; TONG, THI BICH NGUYET; TRAN, THI THANH MAI; DO, THI THU TRANG; DAO, THI XIM; NGUYEN, NGOC HUE; NGUYEN, XUAN HUNG (The journal of contemporary issues in business and government, 2021)
The objective of the paper is to evaluate the impact of corporate social responsibility (CSR) on the performance of Vietnamese seafood exporters by testing multivariate regression models through software SPSS. The study was performed on 315 observations with the surveyed subjects as directors, deputy directors, heads of human resources departments, heads of CSR departments of enterprises operating in the seafood export sector. As a results, CSR has a direct positive impact on the company's performance and has an indirect positive impact on the firm's performance through factors of business values such as employee loyalty, loyalty of customers, corporate reputation and the Government's trust. This result implies that the implementation of CSR will bring positive effects to the business performance, so businesses need to further improve their CSR implementation effectively.